Ischemic Stroke Induced by Bee Sting in Agricultural Society – A Rare Complication of Bee Sting: A Case Report - Navadz, Eqiel; Aprilianto Handoko, Eko; Taufiq, Kamilka; Gemawan, Taufiq; Hakiim, Arsyzilma; Handoko, Adelia; Fortuna Sari, Putri (Faculty of Medicine, Universitas Jember, 2025)
Abstract Introduction: Ischemic stroke is one of the highest causes of morbidity and mortality. One of the factors that triggers ischemic stroke which is quite rare is a bee sting. Pathomechanism of this condition remain unclear. This case report will describe a rare complication of bee sting and discuss it from a pathomechanism perspective. Case Report: A 40-year old woman came to the emergency room at Dr. Koesnadi Bondowoso with the main complaint of weakness in the right face. Referral patients from community health centers. The patient's complaint occurred 7,5 hours ago after being stung by a bee on the middle finger of his left hand. Physical examination showed facial angioedema, edema of digiti manus III sinsitra, and others normal. On neurological examination, it was found: Parasis Nervus XII and VII sinistra UMN type and hemiparasis sinistra. Laboratory examination showed increased neutrophils (90.4%) and eosinophilia (0.1%). A non-contrast CT scan examination showed a hypodense lesion in the right hemisphere. The patient was given antiplatelet, antihistamin, and neuroprotectan. Discussion: One of the rare complications of bee stings is ishemic stroke. This occurs due to the toxin from bee stings which contain vasoactive, pro-inflammatory agents, thrombogenic peptides, thromboxane A2, and leukotrienes which trigger platelet aggregation and vasoconstriction. This condition can trigger trombus formation and lead to ischemic stroke. Medical personnel, especially neurologists, must be aware of pathomechanism from the quite rare complications of ischemic stroke induced by bee stings, especially in rural areas Keywords: Ischemic Stroke, Bee sting, rural area.